PENDIDIKAN MULTIKULTURAL DAN PENANAMAN NILAI-NILAI MODERASI ISLAM DI KALANGAN AHLUSSUNNAH WA AL JAMA’AH - Ridlwan, Burhanuddin (Al Tadib : Jurnal Ilmu Pendidikan, 2019)
Abstract: This article intends to examine multicultural education and the cultivation of moderating values among the Ahlus Sunnah wa al Jama'ah. Through literature studies are produced First, the nature of multicultural education is: An array of beliefs and explanations to recognize and assess the importance of cultural and ethnic diversity in the form of lifestyles, social experiences, personal identities, and educational opportunities of individuals and groups, with the primary goal of change the structure of educational institutions so that students, both students who are members of groups, races, ethnicities, and diverse cultures can have equal opportunities in getting treatment and appreciation. Second, the moderating values of Islam as contained in the Medina charter: The attitude of an egalitarian society, mutual respect, openness, law enforcement and justice, tolerance, deliberation and dialogue. and mutual understanding as in Q.S. al-Hujurat: 13, inclusive attitude in social interaction as in Q.S. al Mumtahanah: 8-9, open attitude and spaciousness as shown by the Prophet SAW when greeting Najran's Christian messenger. Third: multicultural education and the planting of moderating values of Islam among the ahlus sunnah wa al-jama'ah are manifestations in the real form of the principles of ahlussunnah wa al-jama'ah (aswaja) in the form of: Tasawuth, Tawazun, Ta ' adul, and tasamuh. Keywords: Multicultural Education, Moderating Values of Islam, and Ahlussunah Wa al Jama'ah